2017
DOI: 10.18203/2320-6012.ijrms20171825
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis: dermatophytes to yeasts: an experience in and around Mumbai, Maharashtra, India

Abstract: Background: Onychomycosis is a fungal nail infection having wide range of prevalence in different geographical regions. It becomes imperative to know prevalent causative agent in local area to improve quality of life of patients. Present study was aimed to study epidemiological, clinical and laboratory aspects of onychomycosisMethods: Study was carried out prospectively at a tertiary care teaching hospital Nail scrapings of 630 clinically suspected cases of onychomycosis over a period of 5 years (January 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
7
7
2
2
Order By: Relevance
“…Among the dermatophytes isolated, Trichophyton rubrum (15.38%) was predominant followed by Trichophyton mentagrophytes (7.69%) and Trichophyton tonsurans (1.80%). This is similar to studies done by Rupali S. 6 Non-dermatophyte moulds accounts for 25% of the total isolates, of which Fusarium spp. was predominant (5.76%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the dermatophytes isolated, Trichophyton rubrum (15.38%) was predominant followed by Trichophyton mentagrophytes (7.69%) and Trichophyton tonsurans (1.80%). This is similar to studies done by Rupali S. 6 Non-dermatophyte moulds accounts for 25% of the total isolates, of which Fusarium spp. was predominant (5.76%).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the most common age group affected is 21 -30 yrs. followed by 31 -40 yrs., which is in accordance to Veer et al, Rupali S, Shasir W et al and Grover et al 4,6,7 People of this age group are more involved in outdoor activities and are prone to fungal infection due to trauma. Moreover, young population are more apprehensive and regarded it as a cosmetic issue and approach clinician on time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Today, it is known that this condition is not merely a cosmetic concern because there are many clinical conditions such as psoriasis and lichen planus that mimic onychomycosis [ 5 , 7 ]. Moreover, onychomycosis is a source of anxiety, inconvenience, embarrassment, as well as detrimental psychosocial and physical effects [ 3 , 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar to that of earlier studies. 2,4,5 However, in a study done in northern Iran by Falahi AA and his colleagues published at 2017 showed a female preponderance. 6 It is also found that the dermatophyte infection is predominant in the adult age group (31 -40 years).…”
Section: Discussionmentioning
confidence: 99%